2020
DOI: 10.1007/s11356-020-08214-4
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions convergence in Spain: evidence from the club clustering approach

Abstract: This study examines the convergence of greenhouse gas emissions per capita across the 19 Spanish regions using the Phillips-Sul club convergence approach over the period spanning from 1990 to 2017. The results indicate the presence of four clubs which converge to different equilibria in emissions per capita and three clubs in terms of income per capita, which involves different regions. These findings suggest that mitigation policies should explicitly consider the presence of different clubs of regions with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…This has serious implications for human beings and the economy (Acheampong 2019 ; Alshehry and Belloumi 2017 ; Mezghani and Haddad 2017 ). According to Apergis and Garzón ( 2020 ), policymakers are committed to design policies and take national initiatives which help in reducing the adverse impacts of GHG emissions on global environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has serious implications for human beings and the economy (Acheampong 2019 ; Alshehry and Belloumi 2017 ; Mezghani and Haddad 2017 ). According to Apergis and Garzón ( 2020 ), policymakers are committed to design policies and take national initiatives which help in reducing the adverse impacts of GHG emissions on global environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies argue that renewable energy consumption enhances financial and economic development (Kemmler and Spreng 2007 ; Vasylieva et al 2019 ), whereas other extant literature found that FD spurs REC (Apergis et al 2020 ; Ji and Zhang 2019 ; Qamruzzaman and Jianguo 2020 ). Since developed countries work on zero-carbon emission plan (for example see Shahbaz et al 2020 ), emerging economies still account for a significant portion of GHG emissions worldwide (Apergis and Garzón 2020 ; Chen et al 2020 ). Therefore, we intend to highlight the relationship between FD and REC in emerging countries.…”
Section: Introductionmentioning
confidence: 99%
“…An increase/decrease disparity in the GHGs emissions across the countries affect the design and implementation of mitigation policies and the principles used to share the burden of emission reduction. state that if the disparities in GHGs emissions decline (when their overall growth dampens), the distributional impact of the mitigation policies will be less concerning for the policymakers because transfers are reduced across the countries as they converge (Burnett 2016;Apergis and Garzón, 2020). On the contrary, "if differences increase in GHGs emissions, mitigation policies might have distributional cost across countries implying increasing transfers or reallocation of emission-intensive agriculture sector".…”
Section: Insert Figurementioning
confidence: 99%
“…Bulk of the studies examined the "environmental convergence focusing on the ecological footprint (EF) or carbon emissions CO2 or GHGs at the aggregate level" (See, Strazicich and List, 2003;Westerlund and Basher, 2008;Lee and Chang, 2009;Barassi et al, 2011;Acar and Lindmark, 2017;Bilgili and Ulucak 2018;Rios and Gianmoena, 2018;Bilgili et al, 2019;Ulucak and Apergis, 2018;Akram, 2019a, 2019b;Ulucak et al, 2019;Churchill et al 2018Churchill et al , 2020Ivanovski and Churchill, 2020;Ulucak et al, 2020;Apergis and Garzón, 2020;Bhattacharya et al, 2020;Haider, et al 2021;among others). However, the study on the GHGs emissions convergence for the agriculture sector across a large set of countries is limited.…”
Section: Insert Figurementioning
confidence: 99%
See 1 more Smart Citation